Online QoS Modelling Untuk Cloud Menggunakan Teknologi WSN dan IoT Untuk Monitoring CO2 Secara Real-Time - Nurul Fahmi; Rosmida Rosmida; Eko Prayitono (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Wireless Sensor Networks (WSNs) is a technology developed to support one of the smart cities whose the aim is to monitor the environmental conditions CO2, especially regarding data collection to display information on environmental conditions continuously. However, the limitations of this application, it should be noted that the network meets the stringent requirements of the service quality, confidence and high reliability. The goal is strongly influenced by several factors such as environmental characteristics, throughput, and network topology. In this paper, we implementation using real hardware where Arduino as microcontroller and for the monitoring environmental surrounding we use temperature, humidity and CO2 sensors. The data from sensor node will be send to server use IEEE 802.15.4 protocol to data collect and it will be saved to database MySQL. By use IoT technology, the data in the local database will be synchronized to the cloud by using internet access, the aim is so that users can be monitor environment condition by real-time using website or smartphone. In this context, we also provide information on Quality of Service (QoS) management to assist proficiently for monitoring environmental conditions that oversee network performance. The proposed solution proved to be a very useful tool, to detect and clarify potentially throughput and packet lost.